2020
DOI: 10.3390/ma13030793
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Removing from Municipal Solid Waste Incineration Fly Ashes by Electric Field-Enhanced Washing

Abstract: Municipal solid waste incineration (MSWI) fly ash contains chlorides, heavy metals, and organic pollutants, which requires appropriate disposal to eliminate this risk. In this study, the effects of agents on heavy metals removal from MSWI fly ash by electric field-enhanced washing were systematically studied. The results show that when these fly ashes were washed at a current density of 35 mA/cm 2 , polarity switching frequency of 40 Hz, Ethylenediaminetetraacetic acid (EDTA) dosage of 0.5 mol/L, and a pH of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, the effect on the removal of insoluble salt or slightly soluble salt is not good. After washing, heavy metals still cannot meet the requirements of relevant standards [107][108][109]. It can be used in combination with other processing methods.…”
Section: Washingmentioning
confidence: 99%
“…However, the effect on the removal of insoluble salt or slightly soluble salt is not good. After washing, heavy metals still cannot meet the requirements of relevant standards [107][108][109]. It can be used in combination with other processing methods.…”
Section: Washingmentioning
confidence: 99%
“…The recovery of P by wet chemical extraction can be effectively applied to different types of SSA, as they contain higher amounts of P [2,4,[22][23][24][25][37][38][39]. Ashes from wood biomass and MSWI are not as rich in P as SSA, but they are rich in Zn, which is also important to recover [40,44,[49][50][51].…”
Section: Overview Of Extraction Technologiesmentioning
confidence: 99%
“…MSWI-FA is classified as a hazardous waste as it contains soluble salts, dioxins, and a significant amount of heavy metals such as Zn, Pb, and Cd [40]. Due to the presence of potentially leachable contaminants harmful to the environment and human health, landfill sites are becoming fewer, and the possibility of utilizing MSWI-FA has attracted many researchers [27,35,50,51,61,101,102,106]. Sekito et al reported a 2-fold higher content of Zn and Pb in MSWI-FA compared to MSWI-BA, while the content of Cd was even 13-fold higher [107].…”
Section: Potential Use Of Mswi Ashesmentioning
confidence: 99%
“…According to "The Technical Specification for Soil Environmental Monitoring" (HJ/T 166-2004) [25], 0.20 g of dried MSWI fly ash, 6 mL of HNO 3 (69%), 2 mL of HCI (72%), and 2 mL of HF (28%) were added to a digestion tube. The digestion tube was then inserted into the Multiwave Pro and subjected to digestion at 180 degrees for 1 h (Anton Paar, Graz, Austria).…”
Section: Element Analysismentioning
confidence: 99%